2009
DOI: 10.1590/s0100-84042009000400002
|View full text |Cite
|
Sign up to set email alerts
|

Distribuição ambiental e temporal das comunidades de macroalgas de riachos da Serra da Prata, Estado do Paraná, Sul do Brasil

Abstract: -(Environmental and temporal distribution of stream macroalgal communities from Serra da Prata, Paraná State, southern Brazil).Considering the scarcity of studies focusing on stream macroalgal communities in subtropical regions, the present study was conducted to investigate the environmental and temporal distribution patterns of these communities in a well-preserved region of ombrophilous dense forest. Eight samplings sites were sampled twice (Summer and Winter) in the Serra da Prata (SaintHilaire/Lange Natio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
3

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 34 publications
(47 reference statements)
0
6
0
3
Order By: Relevance
“…Cyanobacteria represent common and important members of benthic algal communities of lotic ecosystems around the world (Branco, Necchi Júnior, & Branco, ), and many studies have reported this group as being dominant among primary producers (Peres, Branco, & Krupek, ; Sheath & Cole, ). The great contribution of the cyanobacteria to the richness and abundance of benthic algal communities in streams and rivers has been repeatedly demonstrated worldwide (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Cyanobacteria represent common and important members of benthic algal communities of lotic ecosystems around the world (Branco, Necchi Júnior, & Branco, ), and many studies have reported this group as being dominant among primary producers (Peres, Branco, & Krupek, ; Sheath & Cole, ). The great contribution of the cyanobacteria to the richness and abundance of benthic algal communities in streams and rivers has been repeatedly demonstrated worldwide (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Paraná (KRUPEK et al, 2007;PERES et al, 2008;2009;BRANCO et al, 2008;2009a;2009b), São Paulo (BRANCO; NECCHI, 1996;NECCHI et al, 2000), Rio Grande do Sul (BOHLIN, 1897).…”
Section: Distribuição No Brasilmentioning
confidence: 99%
“…pulvinata também foi encontrada em riachos com substratos rochosos, principalmente aqueles formados por rocha contínua e matacão, porém foram registrados, principalmente, em ambientes sombreados ou parcialmente sombreados. Esse dado corrobora com aquele apresentado por Peres et al (2009), onde E. pulvinata var. pulvinata foi caracterizada como uma espécie indicadora de ambientes sombreados (sensu DeNICOLA, et al 1992).…”
Section: Distribuição Ecológicaunclassified
“…This environment can be characterized by specific environmental factors (e.g., light, nutrients, velocity, temperature and substrate type) which are important for the occurrence and distribution of benthic algae in streams (Sheath et al, 1989;Everitt and Burkholder, 1991;Rosemond and Brawley, 1996). For lotic macroalgae (sensu Sheath and Cole, 1992), recent studies have suggested that variations in the environment in small scale would represent the most important factor for their presence, and each variation would be determined by combinations of specific factors in microhabitat scale (Krupek et al, 2008;Branco et al, 2009;Peres et al, 2009).…”
Section: Introductionmentioning
confidence: 99%